2001
DOI: 10.1073/pnas.251547198
|View full text |Cite
|
Sign up to set email alerts
|

Akt/PKB regulates laminin and collagen IV isotypes of the basement membrane

Abstract: Basement membranes are important for epithelial differentiation, cell survival, and normal and metastatic cell migration. Much is known about their breakdown and remodeling, yet their positive regulation is poorly understood. Our previous analysis of a fibroblast growth factor (FGF) receptor mutation raised the possibility that protein kinase B (Akt͞PKB) activated by FGF is connected to the expression of certain laminin and type IV collagen isotypes. Here we test this hypothesis and demonstrate that constituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 40 publications
(56 reference statements)
2
44
0
Order By: Relevance
“…Overexpression of constitutively active Akt also increased collagen I production in hepatic stellate cells (18) and collagen IV production in embryoid bodies (17). The accumulation of extracellular matrix, including collagen I, is a hallmark of glomerulosclerosis secondary to increased intraglomerular pressure (2,38).…”
Section: Akt Activation Mediates Strain-induced Collagen Production Imentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of constitutively active Akt also increased collagen I production in hepatic stellate cells (18) and collagen IV production in embryoid bodies (17). The accumulation of extracellular matrix, including collagen I, is a hallmark of glomerulosclerosis secondary to increased intraglomerular pressure (2,38).…”
Section: Akt Activation Mediates Strain-induced Collagen Production Imentioning
confidence: 99%
“…Constitutively active Akt or PI3K induced laminin and collagen IV synthesis in embryoid bodies and Chinese hamster ovary cells (17). PI3K was shown to be important in basal production of collagen 1A1 transcript levels in hepatic stellate cells and human lung fibroblasts (18,19).…”
mentioning
confidence: 98%
“…2B). To further determine whether FGF signaling through the PI3K pathway is required for maintaining the undifferentiated status of hESC, we assessed the differentiation of hESCs which were treated with a selective PI3K inhibitor, LY294002 [13]. Regardless of the presence or absence of FGF2 in the media, PI3K inhibition significantly reduced the AP activity (a marker of the undifferentiated state) (Fig.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…This is followed by phosphorylation at serine 473 by a yet-to-be identified mechanism (17). Growing evidence indicates that ANG II/AT-1R signaling induces a crosstalk to the PI3K/Akt pathway (18 -21), and a few studies have shown that these changes in PI3K/Akt activities demonstrated altered phenotypes in collagen synthesis of various types of cells, including MCs (22)(23)(24)(25). These findings suggested that ANG II/AT-1R signaling is implicated in hypersynthesis of collagens in MCs through a crosstalk with the PI3K/Akt signaling pathway and is involved in the development and progression of various kinds of glomerular diseases.…”
mentioning
confidence: 99%